Analisis Technology Acceptance Model (TAM) Dalam Adopsi Digital Payment Syariah - Arian Denopan (Journal of Innovative and Creativity, 2025)
The rapid development of digital technology has transformed global payment systems, including within Islamic finance. Sharia-based digital payments emerge as a solution to support efficient, secure, and Sharia-compliant transactions. This study aims to analyze the adoption of Sharia digital payment systems using the Technology Acceptance Model (TAM) framework through a qualitative approach with a library research method. The findings indicate that perceived usefulness and perceived ease of use remain relevant in shaping user attitudes and behavioral intention, but they are insufficient to fully explain Muslim behavior without considering religiosity, trust, and Sharia compliance. This study highlights that the success of Sharia digital payment adoption is determined by the integration of technological aspects, religious values, and supportive regulations. The implications extend beyond enriching academic literature, providing strategic recommendations for regulators, service providers, and society to strengthen an inclusive and sustainable Islamic digital finance ecosystem.